Natural balancing mechanisms in converters - Van der Merwe, Johannes Wilhelm (Wim) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Electrical and Electronic Engineering))--University of Stellenbosch, 2011.